2013
DOI: 10.1002/wsb.297
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bait tubes for brown treesnake control on guam

Abstract: In 2008, we studied simulated toxicant efficacy to control invasive brown treesnakes (Boiga irregularis) using bait tubes (elongate bait stations that reduce non‐target bait take) in a 5‐ha enclosure in Guam (U.S. Territory) with a known population of snakes. Instead of toxicants, we implanted radiotransmitters in small (6.6 ± 1.4 g) and large (21.8 ± 2.9 g) bait‐mouse carcasses, offered from 2 types of bait tubes over a 3‐month period. The known snake population allowed us to characterize not only the snakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…The effectiveness of various tools for the capture or lethal control of invasive brown treesnakes depends largely on detectability or targetability; that is, given a quantified level of effort, what is the probability of detecting, capturing, or killing an individual snake within the activity area? Effectiveness of visual surveys, trapping, and toxic bait tools for brown treesnake control has been demonstrated to be influenced by internal factors (sex, size, and body condition) and external factors (availability of alternative prey; Gragg et al., ; Rodda, Savidge, Tyrrell, Christy, & Ellingson, ; Tyrell et al., ; Christy, Yackel Adams, Rodda, Savidge, & Tyrrell, ; Lardner et al., ; Christy, Savidge, Yackel Adams, Gragg, & Rodda, ; Siers, Savidge, & Reed, ). These factors have also been indicated to influence brown treesnake movement characteristics (Santana‐Bendix, ; Tobin, Sugihara, Pochop, & Linnell, ; Siers, Reed, & Savidge, ; Christy et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of various tools for the capture or lethal control of invasive brown treesnakes depends largely on detectability or targetability; that is, given a quantified level of effort, what is the probability of detecting, capturing, or killing an individual snake within the activity area? Effectiveness of visual surveys, trapping, and toxic bait tools for brown treesnake control has been demonstrated to be influenced by internal factors (sex, size, and body condition) and external factors (availability of alternative prey; Gragg et al., ; Rodda, Savidge, Tyrrell, Christy, & Ellingson, ; Tyrell et al., ; Christy, Yackel Adams, Rodda, Savidge, & Tyrrell, ; Lardner et al., ; Christy, Savidge, Yackel Adams, Gragg, & Rodda, ; Siers, Savidge, & Reed, ). These factors have also been indicated to influence brown treesnake movement characteristics (Santana‐Bendix, ; Tobin, Sugihara, Pochop, & Linnell, ; Siers, Reed, & Savidge, ; Christy et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These factors have also been indicated to influence brown treesnake movement characteristics (Santana‐Bendix, ; Tobin, Sugihara, Pochop, & Linnell, ; Siers, Reed, & Savidge, ; Christy et al., ). If brown treesnakes decrease movement and foraging during digestion, this will have implications for the effectiveness of various control tools that typically rely either on visual detection by human searchers or response of foraging snakes to lures or baits (e.g., Christy et al., ; Clark et al., ; Engeman & Vice, ; Lardner et al., ; Tyrell et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tyrrell et al () found a minimal positive effect of BCI on female trappability and a negative effect of BCI on male trappability, such that males with low BCIs were caught in baited traps more often. Differently, Lardner et al () found a positive correlation between BCI and accession of bait tubes for both sexes. Our study demonstrated that BCI has a positive effect on AMS and ARS for males, with a similar effect of BCI on ARS supported for females.…”
Section: Discussionmentioning
confidence: 88%
“…During growth, Brown Treesnakes undergo a pronounced ontogenetic shift from a diet consisting almost exclusively of ectothermic prey (small lizards) to endotherms (birds and mammals) as adults [79]. Because current control technologies rely on rodents as trap or toxicant lures, the strong preference of juvenile snakes for small lizard prey renders these tools largely ineffective against snakes in smaller size classes [10,11]. For this reason, along with a snake’s transition into maturity as it grows [12], snake body size is the individual characteristic of greatest importance with respect to its ecology and management.…”
Section: Introductionmentioning
confidence: 99%